2014
DOI: 10.1007/s00429-014-0882-x
|View full text |Cite
|
Sign up to set email alerts
|

The hippocampo-amygdala control of contextual fear expression is affected in a model of intellectual disability

Abstract: The process of learning mainly depends on the ability to store new information, while the ability to retrieve this information and express appropriate behaviors are also crucial for the adaptation of individuals to environmental cues. Thereby, all three components contribute to the cognitive fitness of an individual. While a lack of behavioral adaptation is a recurrent trait of intellectually disabled patients, discriminating between memory formation, memory retrieval or behavioral expression deficits is not e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 29 publications
3
29
0
Order By: Relevance
“…Thus, it is noteworthy that only a fraction of vCA1 and BA neurons labeled selectivity than the dCA1 28,35 . Previous studies have implicated the vCA1 in contextual fear learning 3,6,[36][37][38] . We found that silencing vCA1-BA activity during fear conditioning decreased conditioned fear responses 24 h later, indicating that vCA1-BA activity is involved in the acquisition of contextual fear memory, consistent with a previous report 14 .…”
Section: Discussionmentioning
confidence: 98%
“…Thus, it is noteworthy that only a fraction of vCA1 and BA neurons labeled selectivity than the dCA1 28,35 . Previous studies have implicated the vCA1 in contextual fear learning 3,6,[36][37][38] . We found that silencing vCA1-BA activity during fear conditioning decreased conditioned fear responses 24 h later, indicating that vCA1-BA activity is involved in the acquisition of contextual fear memory, consistent with a previous report 14 .…”
Section: Discussionmentioning
confidence: 98%
“…Functionally, the reduction of excitatory synapse number results in a little, not significant reduction of mEPSC and in LTP impairment only with a paradigm of theta burst stimulation (LTP for high‐frequency stimulation is comparable to WT mice). Data of behavioral studies show that IL1RAPL1 knockout male mice show deficits in spatial recognition, and fear memories (Pavlowsky et al , ; Houbaert et al , ; Yasumura et al , ; Zhang et al , ; Montani et al , ). Social interaction and motor coordination are improved in IL1RAPL1 knockout mice, but the motor learning ability is comparable with wild‐type mice (Yasumura et al , ).…”
Section: Il1rapl1 Knockout Micementioning
confidence: 99%
“…Present studies with mutant mice revealed that the ablation of IL1RAPL1 affects diverse brain functions including learning, memory, behavioral flexibility, locomotor activity, and anxiety (Pavlowsky et al , ; Yasumura et al , ; Zhang et al , ; Montani et al , ). In particular, hippocampal‐dependent memory is strongly impaired.…”
Section: Il1rapl1 Knockout Micementioning
confidence: 99%
See 2 more Smart Citations